Distribution of erythrocyte binding antigen 175 (EBA-175) alleles and ABO blood groups in a hypoendemic area in Senegal - Aida Sadikh Badiane; Ousmane Sarr; Awa Bineta Deme; Ambroise Dioum Ahouidi; Papa Elhadji Omar Gueye; Mouhamadou Ndiaye; Mame Cheikh Seck; Mouhamadou Diallo; Amy Kristine Bei; Manoj T Duraisingh; Dyann Wirth; Daouda Ndiaye; et al. (Journal of Infection in Developing Countries)
Introduction: The study was conducted to determine for the first time the association between the erythrocyte binding antigen 175 (EBA-175) alleles and ABO blood groups in malaria patients living in Thies, a hypoendemic area in Senegal. Methodology: In 2007, the EBA-175 alleles and blood group types were determined by nested PCR and the Simonin test respectively in blood samples obtained from uncomplicated Plasmodium falciparum malaria positive patients. Results and conclusion: In total, 129 patients were enrolled in the study. The EBA-175 genotyping showed a prevalence of 67.45% for the F-allele, 27.90% for the C-allele and 4.65% of mixed C+F infection. The distribution of the ABO blood group type showed 59.8% for the O group, 19.7% for the A group, 17.2% for the B group, and 3.3% for the AB group. No correlation was noted between the EBA-175 alleles and either the blood group type or parasitemia.